Variabilidade no andar com ultrapassagem de obstáculo de idosos com doença de Parkinson - Simieli, Lucas [UNESP] (2015)
The degeneration of dopaminergic neurons of the substantia nigra leads to signs and symptoms of Parkinson's disease (PD). Furthermore, it is common that PD people have gait changes, also changing the gait variability. The variability of gait parameters has been used as an important tool to identify fallers and dementia. The aim of the study is to analyze the spatial variability of gait parameters in patients with PD during the obstacle avoidance of different heights, and after, identify predictive parameters of falls in older adults with PD and healthy neurologically individuals. Study participants were 78 elderly (39 elderly people with PD and 39 neurologically healthy individuals). In order to answer the questions, three studies were proposed. For Studies 1 and 2, participated 28 individuals (15 individuals with PD and 13 neurologically healthy individuals). The task consisted at walking on a walkway (8 meters long) at preferred speed. The foam obstacle was positioned in the middle of the walkway during the conditions of the adaptive floor. For the approach phase four steps before the obstacle were used. For obstacle avoidance, only the “avoidance step” of both the leading limb and the trail limb were used in the analysis. We also calculated the horizontal and vertical distances from the obstacle. The results revealed greater variability to the nearest obstacle to the steps. Furthermore, the obstacle height is an important factor in these phases. The low obstacle proved to be as challenging as the high obstacle, increasing the variability in both groups. In Study 3, participants were distributed into 4 groups (PD fallers and non-fallers, neurologically healthy elderly fallers and nonfallers). Procedures, experimental design and methodology were similar to Study 1, but the obstacle height was only one (low). To acquire the gait parameters in the three studies we used an optoelectronic device movement analysis (Optotrack®) and a carpet with pressure sensors (GAITrite®). Also two force plates (AMTI®) were positioned on the walkway for the acquisition of kinetic parameters. The ROC analysis was used to determine the predictors of falls in this population. The results indicate important parameters for predicting falls, especially in the approach phase, where the first steps (further to the obstacle) were good classifiers to determine fallers. In addition, the horizontal distance between foot and the obstacle also performed well to classify as elderly fallers. Consider the fallers as those that fell two or more times in the period is an effective strategy, it helps in differentiating the group, making it more reliable analysis.